State roles in providing affordable mass transport services for low-income residents - Robert Cervero (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2011)
Governments support urban mass transport services worldwide under the guise of helping the poor and improving the environment. With more and more governments cash-strapped and facing budgetary shortfalls in other vital areas, the fiscal burdens of underwriting public transport have prompted some observers to question such rationales. This paper reviews the role of states in ensuring affordable mass transport services are available to low-income residents. The heavy financial burdens that the poor sometime face in moving about the city and possible ways of reducing these impacts are discussed. Examples of keeping transit fares affordable while also ensuring reasonably cost-effective mass transport services are cited. Because public policy choices that shape mass transport services are informed by technical evaluations, this paper also examines conventional practices regarding how transport proposals are reviewed and assessed. It argues that moving toward a framework that focuses on enhancing accessibility rather than principally mobility would better represent the long-term impacts of capital investments while also promoting the interests of mobility-disadvantaged populations.
Keywords: 330